GeneXpert positivity and evaluation of rifampicin resistance among endometrial biopsy specimens for the diagnosis of Genital Tuberculosis - Bineeta Kashyap; Dibyashree; Rituparna Saha; N. P. Singh; Puneeta Hyanki; Ashwani Khanna (Barpeta Obstetrics and Gynaecological Society, 2020)
Objective: The aim of this study was to find out the GeneXpert positivity among endometrial biopsy specimens for diagnosis of genital tuberculosis. Materials and Methods: A retrospective study was conducted from January 2019 to June 2019 on all women clinically and radiologically diagnosed with infertility, dyspareunia, menstrual irregularities and pelvic inflammatory disease. Endometrial biopsies were taken from all cases and subjected to GeneXpert test for detection of Mycobacterium tuberculosis. Result: Total number of suspected cases was 62 with age ranging from 19 years to 65 years. Majority of suspected cases were from the age group 21-30 years (54.8%). Five out of 62 (8%) cases tested positive for Mycobacterium tuberculosis by GeneXpert which were all sensitive to Rifampicin. Among these 5 cases, 2 were reported as medium positive and 3 as very low positive based on cycle threshold value. Conclusion: GeneXpert on endometrial biopsy may prove to be a reliable diagnostic modality for genital tuberculosis as well as multidrug resistance tuberculosis in females leading to timely management of the disease.